A.A.V.V., El Islam y Occidente, Barcelona, Editorial Océano, 2004, 384 págs., I.S.B.N.84-494-2551-4. - Arroñada, Silvia Nora (2007)
Fil: Arroñada, Silvia Nora. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales; Argentina